Importance of industrial training for young women - Dille, Cassie Belle (My University, 1898)
Introduction: It has been said, “Mans first necessity is to live, and his first duty to work;” but at no time in the history of the world has the problem of how to live and to earn a living, been of greater importance than at present. Our streets swarm with loafers, our highways with tramps, and we find our prisons crowded to overflowing with criminals, all because of the lack of fitness necessary for the earning of an honest living.
Citation: Dille, Cassie Belle. Importance of industrial training for young women. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Man; Work; Duty; Criminals; Theses; Manuscripts (documents)